Effects of Snow and Ice on Waterfowl Distribution in the Central Canadian Arctic Islands - McLaren, Margaret A.; Alliston, W. George (ARCTIC, 1985)
Aerial surveys were conducted in 1974 and 1975 to determine distribution and abundance of waterfowl along the coasts of Somerset, Cornwallis, Little Cornwallis, and Byam Martin islands, Boothia Peninsula, as well as parts of Prince of Wales, Devon, Bathurst, and Melville islands. Waterfowl nested normally in 1975 but were prevented from doing so in 1974 by a late thaw. In 1974, but not in 1975, Barrow Strait was ice free by 1 June. Densities of most species were lower in spring 1975 than in 1974, when inhospitable conditions inland forced the birds to concentrate in coastal areas. In late summer Brant (Branta bernicla) and Oldsquaw (Clangula hyemalis) were more numerous in 1975 than in 1974; Brant left the central High Arctic in midsummer 1974, but the reason for the smaller number of Oldsquaw is not evident. Both Snow Geese (Chen caerulescens) and eiders (Somateria spp.) were more abundant in late summer 1974 than in 1975. Many Snow Geese moved to southeastern Somerset Island and adjacent waters to moult in 1974. In 1975 many eiders and Snow Geese remained at inland locations with their broods. Queens Channel, northern Somerset Island and Bellot Strait were particularly important to waterfowl, irrespective of spring phenology. Melville and Byam Martin islands were used by Brant, and Canada Geese (Branta canadensis) occurred mainly on the Boothia Peninsula. Snow Geese were abundant in both years in southeastern Somerset Island, particularly near Creswell Bay, where both breeding and moulting occurred. Coastal waters of Barrow Strait, Prince Regent Inlet and the Gulf of Boothia were heavily used by Oldsquaw in spring and summer, and Crooked Lake, Prince of Wales Island, was used by many moulting Oldsquaw in both years. Common Eiders (S. mollissima) occurred principally in Queens Channel, Barrow Strait and near Bellot Strait; King Eiders (S. spectabilis) also concentrated in the same areas but were more widely distributed throughout the study area.Key words: Arctic Islands, N.W.T., waterfowl distribution, ...